The Development and Progression of Micro-Nano Optics - Wang, Yong; Yang, Jie; Wang, Zhiwei; Kong, Xiaofei; Sun, Xiangyu; Tian, Jingjing; Zhang, Xiushuo; Zhao, Xiaolong; Liu, Yanping; Li, Hongsheng; Su, Yuqing; Hao, Xiaorui; et al. (Frontiers in Chemistry, 2022)
Micro-Nano optics is one of the most active frontiers in the current development of optics. It combines the cutting-edge achievements of photonics and nanotechnology, which can realize many brand-new functions on the basis of local electromagnetic interactions and become an indispensable key science and technology of the 21st century. Micro-Nano optics is also an important development direction of the new optoelectronics industry at present. It plays an irreplaceable role in optical communication, optical interconnection, optical storage, sensing imaging, sensing measurement, display, solid-state lighting, biomedicine, security, green energy and other fields. In this paper, we will summarize the research status of micro-nano optics, and analyze it from four aspects: micro-nano luminescent materials and devices, micro-nano optical waveguide materials and devices, micro-nano photoelectric detection materials and devices, and micro-nano optical structures and devices. Finally, the future development of micro-nano optics will be prospected.